Factors related to positive detection of Acinetobacter Baumannii on the hands of medical-staff in Shanghai - ZHANG Xing; TIAN Liang; ZHANG Hongzhi; GE Yilin; JI Xiaofan; ZHU Renyi; HUANG Lyulan (Shanghai yufang yixue, 2022)
ObjectiveThis study aimed to investigate the risk factors affecting the positive detection of Acinetobacter baumannii on the hands in medical staff of hospitals in Shanghai， and provide epidemiological evidence for the prevention and control of nosocomial infections.MethodsThe hands of doctors， nurses and care workers in key departments were sampled every quarter from 2018 to 2020 according to GB 15982‒2012 "Hospital Disinfection and Hygiene Standards". Separation and identification of A. baumannii were followed with sampling shortly. Information about the working years of sampling subjects， the hand sanitizers of which sampling subjects had used and the ingredients and actual using time of the hand sanitizers was collected while sampling. Finally， 709 samples were selected for this research after excluding the unqualified samples.ResultsThe positive detection of the hand samples was 7.05%. The logistic regression model suggested that the department， the time of using hand sanitizer， the hospital grade and occupational category were determinants of A. baumannii positive detection on hands in medical staff. The risk of A. baumannii positive detection in internal medicine department was 2.846 （95%CI：1.402‒5.776） times higher than that in intensive care unit while it was 3.357 （95%CI：1.349‒8.353） times higher in surgery department than that in intensive care unit. Regarding the use of hand sanitizer， the risk of A. baumannii positive detection was 3.076 （95%CI：1.534‒6.168） times higher in the staff used the hand sanitizer over 14 days than in the medical staff used the sanitizer within 14 days. The risk of A. baumannii positive detection in medical worker in secondary hospitals was 2.235（95%CI：1.088‒4.588）times than in tertiary hospitals. The risk of A. baumannii positive detection of care workers was 3.634 （95%CI：1.764‒7.484） times higher than nurses.ConclusionThe positive detection of hand samples was 7.05%. Department， the time of using hand sanitizer， the hospital grade and occupational category were determinants of A. baumannii positive detection on hands in medical staff. It was necessary to improve hand hygiene for medical staff， especially for care worker. Cleaning and disinfection need to be strengthened in internal department and surgery department.